Exploring the perceptions of service providers on the availability and effectiveness of sexual violence interventions, services and programmes in De Aar - Alexander, Jacoline R M (2020)
The aim of this study was to explore the perceptions of service providers on the availability and effectiveness of sexual violence interventions, services and programmes in De Aar. Participants were selected based on the nature of service they rendered to survivors of sexual violence. A qualitative study was conducted, using non-probability purposive sampling and snowball sampling. Data was gathered through a semi-structured interview. The study found protection services, medical and psychological interventions to be easily accessible to all survivors of sexual violence. Additional services were also found to be available to survivors of sexual violence, depending on their needs. Participants were all of the opinion that the needs of survivors were being met in De Aar. The data found the perceptions of service providers on the effectiveness of their interventions to be influenced by their adherence to regulations and training received through their organisations, in addition to personal steps taken to develop professional skills. The attitude of service providers and the co-operation of service users were found to hinder the effectiveness and consistency of prescribed interventions. Gaps found to be inherent in all organisations were lack of human and physical resources such as vehicles. Stakeholders were found to be ineffective in their communication and co-operation between stakeholders was inadequate. Challenges found to hinder help-seeking were the perceptions of the community of the South African Police Service and sexual violence in general. The survivors themselves were also identified as a barrier to intervention, as they might accept, reject or discontinue intervention without warning. Considering the aim and objective of this study, it can be concluded that there are services in place for survivors of sexual violence in De Aar. Immediate services, such as post-rape medical and legal services, are easily accessible. Follow-up and aftercare service are determined by a social worker and most organisations are effective in the services they render, despite organisational challenges and limitations